2014
DOI: 10.1002/ppul.22995
|View full text |Cite
|
Sign up to set email alerts
|

Neurally adjusted ventilatory assist (NAVA) in pediatric intensive care—A randomized controlled trial

Abstract: We found NAVA to be a safe and feasible primary ventilation mode for use with children. It outscored standard ventilation in some aspects, as it was able to enhance oxygenation even at lower airway pressures and led to reduced use of sedatives during longer periods of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 23 publications
4
79
0
Order By: Relevance
“…First and most importantly, the lack of randomization, which makes it impossible to exclude that part of our results were actually a consequence of a time-dependent carryover effect, or of the evolution of the lung disease, more than to differences between modes. Nonetheless, most of our findings are consistent with previously published work [5,6,7,8,9,10,11,23]. In addition, the severity of the disease, as defined by the OI and PcO 2 /FiO 2 , did not significantly change during the 24-hour study period, as depicted in table 2.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…First and most importantly, the lack of randomization, which makes it impossible to exclude that part of our results were actually a consequence of a time-dependent carryover effect, or of the evolution of the lung disease, more than to differences between modes. Nonetheless, most of our findings are consistent with previously published work [5,6,7,8,9,10,11,23]. In addition, the severity of the disease, as defined by the OI and PcO 2 /FiO 2 , did not significantly change during the 24-hour study period, as depicted in table 2.…”
Section: Discussionsupporting
confidence: 82%
“…In keeping with previous data [5], fewer sedatives were required during NAVA, as opposed to PRVC. Very recently, Kallio et al [23] reported reduced administration of sedatives during NAVA in a subgroup of nonsurgical infants, compared to current standard conventional ventilation. Although our sedation policy is in agreement with the available recommendations [15], no score or scale for evaluating discomfort, pain, or agitation was utilized.…”
Section: Discussionmentioning
confidence: 99%
“…In ventilated children, NAVA often induced a significant decrease in inspiratory airway pressures [8,9]. Consistent with these data, NAVA was considered as ventilation mode to support a child with a large BPF and refractory hypoxemia despite conventional ventilation.…”
Section: Case Descriptionsupporting
confidence: 56%
“…A recent randomised controlled trial comparing NAVA to conventional ventilation modes (pressure control and pressure regulated volume control) in 170 critically ill children reported a halving in the ventilation duration with NAVA (3.3 hours compared to 6.6 hours) though this did not reach statistical significance. Sedative doses were also lower in children admitted for medical reasons though not when surgical patients were included in the analysis (Kallio et al, 2015). This trial suggests NAVA is a feasible and safe ventilator mode for children at least.…”
Section: Patient-ventilator Interactionmentioning
confidence: 81%